Estrus Synchronization and Artificial Insemination in Goats during Low Breeding Season-A Preliminary Study - A. Mehmood*, S. M. H Andrabi, M. Anwar and M. Rafiq (Pakistan Veterinary Journal, 2011)
A pilot project was initiated to introduce artificial insemination (AI) in goats at farmer level with chilled semen. Does (n=18) were synchronized with progesterone impregnated vaginal sponges (60 mg Medroxyprogesterone acetate; MAP) for 11 days. At 48 hrs prior to removal of the sponges, intramuscular injection of 400 IU equine chorionic gonadotropin (eCG) and cloprostenol (0.075 mg) was given. Fixed time vaginal insemination (43-45 hrs after sponge removal) was done twice (at 12 hrs interval) in 17 does with chilled Beetal buck semen (4°C) extended with Tris-citric acid (TCA) or skimmed milk (SM) based extender (75 x 106 sperm/ml). Pregnancy test was performed at 45 days post insemination through ultrasonography. An overall 94.5% (17/18) of does showed heat signs and 78% of them were detected in heat between 12 - 24 hrs after sponge removal. An overall 29.4% (5/17) pregnancy rate was recorded. Higher pregnancy rate (44.4%) was obtained in does inseminated with SM extended semen as compared to 12.5% for TCA extended semen. Results were encouraging in the sense that to the best of our knowledge it was the first report of kidding through AI in heat induced does in Pakistan. Moreover, it indicated the feasibility of using synchronization and fixed time AI during low breeding season to enhance the reproductive efficiency in local goats.